Determinants of Residential Location Decisions among the Pre-Elderly in Central Ohio - Hazel A. Morrow-Jones; Moon Jeong Kim (Journal of Transport and Land Use, 2009)
This paper examines the differences and similarities in residential movement patterns and motivations between young households (under 50), pre-elderly households (50 through 64) and elderly households (65 and over). We use deed transfer records and a survey of home owners who moved between late 2004 and early 2006 in Franklin County, the central county of the Columbus, Ohio metropolitan area. The patterns are mapped and the motivations and household characteristics are explored through descriptive analysis and discriminant analysis. Most expectations are supported and the pre-elderly are seen to be a distinct group with some similarities to each of the other two age cohorts, but also some unique characteristics and interests.